FEATURES VEGETATIVE REGULATION OF THE HEART RATE IN PRETERM INFANTS WITH HYPOXICHEMORRHAGIC DISORDERS OF THE BRAIN - B.A. Bezkaravayny; G.A. Solovyova (Bukovynian State Medical University, 2013)
In article are present the results of 24-hour monitoring of ECG 65 preterm infants with hypoxic-hemorrhagic CNS. Analysis of heart rate variability revealed the predominance of sympathetic activity with inhibition of parasympathetic activity, which leads to a sharp voltage compensatory mechanisms with possible further development of the dysrhythmia. Oxygenotherapy, which is held on time and effectively, helps reduce stress and normalization of autonomic balance by moving to a system of regulation of the operation of the infant, which the body stores energy.